IOT Based Approach On Aquarium Monitoring System With Fish Feeder Automation - Mat tahir, Nurul Huda; Mohamad, Safuan Naim bin; Wan Tarmizi, Wan Faizura; Muhd Zain, Muhammad Luqman (Journal of Engineering and Technology (JET), 2020)
Abstract— The monitoring system is known to be very useful for alleviating human activities and can been utilized in many ways. The idea to automate the monitoring system originated from a couple of problems. The time consuming process for manually checking and measuring every parameter at every part in an aquarium is one of the problem. The second problem is the lack of availability of time to keep the aquarium meeting the mandatory fish needs that need to be reviewed regularly. Along with these there are known that important parameters such as condition of pH water and the availability of food is essential to keep the habitat conducive for living. Therefore this paper proposed an aquarium monitoring system utilizing Internet of Thing (IoT) with automatic fish feeder. With the existence of IoT system, user can be continuously notified in real time. The monitoring system is utilized as a platform to remind the user to clean or filling food in the feeder when necessary. The system also equipped with automatic feeder fulfilling the fish mandatory needs. The result showed that the developed system able to display the current conditions of pH water value and the level of the fish food through Blynk application. This user friendly and compact fish tank design can be implemented almost anywhere.